(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The purpose of this article is to clarify the changes in linguistic systems in today’s era of globalization, the use of lexical items in the English language, the impact of ICT on international integration, and the formation and differentiation of lexical items.